Effectiveness of Physical Fitness and Training Facilities in Enhancing Volleyball Athlete Performance: The Mediating Role of Mental Readiness (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
This study investigated the contributions of physical fitness and training facilities to volleyball athlete performance within an integrated framework incorporating mental readiness. The research was motivated by suboptimal regional competitive achievements, highlighting the need for an evidence-based athlete development approach. A quantitative cross-sectional survey design was employed. The data were analyzed using covariance-based Structural Equation Modeling (SEM) with AMOS. The sample consisted of 120 active volleyball athletes representing several clubs and competitive levels from 12 regencies and cities in South Sulawesi under the supervision of local PBVSI organizations. Instrument validity and reliability were confirmed through Confirmatory Factor Analysis prior to testing the structural relationships. The results revealed that physical fitness and training facilities had significant positive direct effects on athletic performance and also significantly influenced mental readiness. However, mental readiness did not demonstrate a statistically significant direct relationship with performance. The structural model achieved acceptable goodness-of-fit indices, indicating adequate model fit. Overall, the findings suggest that volleyball performance is primarily influenced by physiological capacity and infrastructural support, while psychological readiness serves as a complementary factor in athlete development.